Impact of vaccines on antimicrobial resistance - Buchy, Philippe; Ascioglu, Sibel; Buisson, Yves; Datta, Sanjoy; Nissen, Michael; Tambyah, Paul Anantharajah; Vong, Sirenda (International journal of infectious diseases, 2020)
[Display omitted] •The inappropriate use and overuse of antibiotics accelerates antimicrobial resistance (AMR).•New antibiotic development has declined sharply in recent years.•A significant rise in deaths and medical costs from antibiotic-resistant bacterial infections could result by 2050.•Vaccines can prevent bacterial and viral infections from occurring and spreading.•Preventing infections and their transmission should reduce antibiotic use and AMR. Antibiotic use drives the development and spread of resistant bacterial infections. Antimicrobial resistance (AMR) has become a prolific global issue, due to significant increases in antibiotic use in humans, livestock and agriculture, inappropriate use (under-dosing and over-prescribing), and misuse of antibiotics (for viral infections where they are ineffective). Fewer new antibiotics are being developed. AMR is now considered a key threat to global health, leading to more mortality and increased healthcare costs threatening future conduct of routine medical procedures. Traditional approaches to address AMR include antibiotic stewardship, better hygiene/infection control, promoting antibiotic research and development, and restricting use for agricultural purposes. While antibiotic development is declining, vaccine technology is growing. This review shows how vaccines can decrease AMR by preventing bacterial and viral infections, thereby reducing the use/misuse of antibiotics, and by preventing antibiotic-resistant infections. Vaccines are less likely to induce resistance. Some future uses and developments of vaccines are also discussed. Vaccines, along with other approaches, can help reduce AMR by preventing (resistant) infections and reducing antibiotic use. Industry and governments must focus on the development of novel vaccines and drugs against resistant infections to successfully reduce AMR. A graphical abstract is available online.